2006
DOI: 10.1088/1742-6596/49/1/005
|View full text |Cite
|
Sign up to set email alerts
|

Probing the shell model using nucleon knockout reactions

Abstract: Abstract. We assess the sensitivity of the intermediate energy, direct two-nucleon knockout reaction mechanism to details of the correlated motions of the two removed nucleons -as might be revealed by measurements of partial cross sections to different final states of the mass A−2 reaction residues. Comparisons of new reaction calculations with recent data for exotic nuclei in the sd-shell suggest that this sensitivity is significant and that the coherence of the twonucleon configurations to the reaction allow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…This is a robust quantity independent of unobserved higher lying transitions. This value is reproduced by all calculations and is substantially larger than the ∼25% value expected if the protons were uncorrelated [18], reflecting the enhanced spatial correlations associated with time-reversed J = 0 + pairs. The 1443 keV transition is placed in cascade with the 792 keV transition and could correspond to the decay from either of the J = 4 (Fig.…”
mentioning
confidence: 61%
See 1 more Smart Citation
“…This is a robust quantity independent of unobserved higher lying transitions. This value is reproduced by all calculations and is substantially larger than the ∼25% value expected if the protons were uncorrelated [18], reflecting the enhanced spatial correlations associated with time-reversed J = 0 + pairs. The 1443 keV transition is placed in cascade with the 792 keV transition and could correspond to the decay from either of the J = 4 (Fig.…”
mentioning
confidence: 61%
“…There, and more recently in [16,17] for the associated momentum spectra of the two-nucleon removal reaction residues, it is shown that the reaction dynamics restricts these direct removal events to grazing collisions between the projectile and target. This defines a (near cylindrical) volume through the projectile surface in which the collision with the target samples the joint position and momentum amplitudes of the wave functions of the two removed nucleons [18]. The shell model then provides this two-nucleon amplitude information.…”
mentioning
confidence: 99%
“…2 and 3 of Ref. [18], and will be emphasized here, the total angular momentum of the final state and the detailed TNA of the wave function can strongly affect the two-nucleon joint position probability, its projection and the magnitude of the removal cross sections. The (shell-model) structural correlations may also enhance or suppress particular total orbital angular momenta and so may affect the residue momentum distributions also.…”
Section: A Two-nucleon Joint Position Probabilitymentioning
confidence: 87%
“…The structure input now enters in the form of the initial-state to final-state two-nucleon overlap function, in which the two active (valence) nucleons are correlated and their configurations appear coherently. The sensitivity of two-nucleon knockout reaction yields to these two-nucleon correlations has been discussed in some detail elsewhere [21,23,29,30]. This is not our prime interest here.…”
Section: Introductionmentioning
confidence: 89%